2004
DOI: 10.1179/joc.2004.16.4.392
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Vinorelbine and Docetaxel as Second-Line Chemotherapy for Pretreated Non-Small Cell Lung Cancer Patients: a Phase I-II Trial

Abstract: Docetaxel was proven to be effective as second-line therapy for patients with advanced NSCLC after failure of platinum-based front-line chemotherapy. We designed this phase I/II study to define the Maximum Tolerated Dose of weekly docetaxel combined with weekly vinorelbine, and subsequently evaluate tolerability and activity of this schedule in NSCLC patients who were progressive after treatment with either cisplatin and gemcitabine or carboplatin and paclitaxel regimens. To be eligible for the study, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, the overall survival is only 7-8 months with overall response rates reported lower than 10% and 1-year survival rate of 30% [20,22,23,25]. Several trials have been published investigating combination therapies based on docetaxel, gemcitabine or vinorelbine [26][27][28] but the median overall survival remains in the range of 6-8 months and therapyassociated toxicity seems to be relatively high in most of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall survival is only 7-8 months with overall response rates reported lower than 10% and 1-year survival rate of 30% [20,22,23,25]. Several trials have been published investigating combination therapies based on docetaxel, gemcitabine or vinorelbine [26][27][28] but the median overall survival remains in the range of 6-8 months and therapyassociated toxicity seems to be relatively high in most of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have been published investigating combination chemotherapy using two non-platinum agents for recurrent NSCLC in randomized clinical trials, with the objective of improving outcomes further. However, none of these studies have demonstrated improved survival with combination chemotherapy, whereas there have been relatively higher or intolerable toxicities [13][14][15][16]. Therefore, more active regimens for the second-line chemotherapy are much needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been relatively higher or intolerable toxicities observed in this context (Pectasides et al , 2001; Spiridonidis et al , 2001; Nelli et al , 2004; Takeda et al , 2009). In the present study, we evaluated the efficacy and safety of a new scheduled combination of S-1 and docetaxel, each of which have shown promising efficacy in the treatment of advanced or metastatic NSCLC.…”
Section: Discussionmentioning
confidence: 99%